Egg and Broiler Supply in Malaysia: Issues, Challenges and Recommendations - Jamaludin, Mohd Hafiz; Jalil Marsal, Cristilina; Chowdhury, Ahmed Jalal Khan; Tuan Harith, Zuharlida; Mohamed Ridzwan, Raimi; Abdul Kari @ Abdullah, Zulhisyam (Halalsphere, 2023)
The Malaysian poultry industry, particularly the broiler and egg supply, was greatly affected due to recent global challenges such as COVID-19, the Russia-Ukraine conflict, global logistic strains, and the overall deceleration of economies. Being self-sustainable for poultry, the crisis throughout 2022 has shown how fragile the industry is in Malaysia. Based on the above perspectives, the dependency of the poultry industry on imported feed materials and its stability from external factors that support the industry needs to be considered to sustain food security. Therefore the concept of food security in a country might need to be further evaluated as a sustainable value chain rather than individual components. Understanding the value chain involved in the poultry industry is important to conclude the decisions to attain supply stability in Malaysia.